Integrasi Nilai Sosial dan Budaya dalam Struktur Arsitektur Tradisional Buton (Analisis Fungsi dan Makna Ruang) - Rafi, Abdur; Pare Eni , Sri; P Pasaribu , Ramos (JURNAL TEKNIK, 2024)
Traditional architecture in Buton, Southeast Sulawesi, reflects a deep connection between social values, culture, and belief systems of the community. Traditional Butonese buildings, such as the kamali (the Sultan's traditional house), integrate kinship values, social structures, and religious aspects that are passed down from generation to generation. This article explores how these social and cultural values ​​are integrated into the spatial layout and function of traditional buildings, and explores the symbolic meaning of architectural elements. Using a qualitative approach with ethnographic methods, this study analyzes the function of space, social hierarchy, and beliefs embedded in Butonese architecture. The results show that the spatial layout in traditional Butonese architecture not only functions practically but also symbolically, reflecting a cultural identity that continues to live in modern society.